Medical Management of Trigeminal Neuralgia with Carbamazepine, Gabapentin and Pregabalin: A Randomized Placebo Controlled Trial - Hercules, Simon; Neelakandan, RS; Bhargava, Darpan; Arnold, Joseph (Journal of Orofacial Research, 2014)
Trigeminal neuralgia (TN) or Tic douloureux is a disorder characterized by stabbing or electric-shock-like pain in parts of the face. The presented research evaluates the use of gabapentin and pregabalin with carbamazepine to relieve neuropathic pain in this condition.